ANALYSIS OF THE REGIONAL DISTRIBUTION, PATTERNS AND FORECAST OF ROAD TRAFFIC FATALITIES IN GHANA - Ofosu, John B.; Hesse, Christian A. (European Scientific Journal, ESJ, 2014)
Road traffic fatalities (RTFs) in Ghana have adverse effect on the dependency ratio and economic growth in the formal sector of the economy. To analyse the pattern of road traffic deaths in Ghana, fatalities of road traffic accidents by age group from 2001 – 2010 were obtained. Using published road traffic accident statistics from the National Road Safety Commission of Ghana, the pattern of RTF in the ten (10) geographical regions in Ghana was obtained, using moving average analysis. The pattern of the road traffic fatality data displays 10 distinct yearly cycles over a 10- year period, with the underlying trend showing a steady marginal increase overall, as well as in each particular region. Based entirely on the moving average trend of the past data, the values of the number of RTFs are projected for each of the 10 geographical regions. The number of road traffic fatalities in Ghana are predicted to rise from 1 986 in the year 2010 to 3 526 in the year 2030, an increase of about 77.5%. This finding is consistent with one of the key findings on global trends and projections presented in the World report on road traffic injury prevention, which revealed that road traffic deaths are predicted to increase by 83% in low-income and middle-income countries.